El individuo inquietante en la película "Aguirre, la cólera de Dios" de Werner Herzog - Neira, Hernán (Revista de Filosofía, 2007)
In the following pages, inspired by Sartre’s concept of "regard" and Foucault’s concept of "panopticon," we consider the role of regarding and of panoptical watching in the film Aguirre, God’s Wrath (Aguirre, der Zorn Gottes), by Werner Herzog. We point out how the bodies of Aguirre’s fellow conquistadors are dominated by him; how, by this relation they are transformed; and, finally, we discuss the meaning and nature of the film, which is more linked with the representation of a sublime individual (in the Kantian sense of the word erhaben) than with a mere story about the American Conquest.